2017
DOI: 10.1017/s0950268817000437
|View full text |Cite
|
Sign up to set email alerts
|

Differences between migrants and Spanish-born population through the HIV care cascade, Catalonia: an analysis using multiple data sources

Abstract: Migrants are considered a key group at risk for HIV infection. This study describes differences between migrants and the Spanish-born population as they progress through the HIV care cascade in Catalonia, Spain. This study found that among people reached by prevention activities, migrants had a higher number of barriers to access HIV testing services than Spanish-born people, driven primarily by shared risk factors. Between 2001 and 2013, 9829 new HIV diagnoses were reported in Catalonia, the proportion of mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
2
12
0
1
Order By: Relevance
“…However we did not collect data to compare with non-migrants. Another study found higher default rates among migrants compared to Spanish born populations (9.2% versus 6.3%) [ 13 ]. On the contrary, a study in Johannesburg, South Africa, found default rates to be significantly lower in foreigners compared to local citizens (12% versus 31%) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However we did not collect data to compare with non-migrants. Another study found higher default rates among migrants compared to Spanish born populations (9.2% versus 6.3%) [ 13 ]. On the contrary, a study in Johannesburg, South Africa, found default rates to be significantly lower in foreigners compared to local citizens (12% versus 31%) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 23 In Catalonia, this could be explained by the fact that migrants experienced a higher number of barriers to access HIV testing services than the Spanish-born population and that these needs might be driven primarily by shared risk factors. 24 This also can be due to the fact that migrants face cultural and linguistic barriers as well as legal and administrative impediments to accessing health services and thus HIV testing facilities. 25 In Europe, the HIV testing uptake among migrants range from 23% to 64%.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of new infections decreased in Australia, particularly among men who have sex with men (MSM), new HIV infections among migrants increased [6]. Migrants were also more likely to present with a late HIV diagnosis than citizens [6,8,9]. These differences raise concerns that migrants are being 'left behind', highlighting the need to focus on this group if Australia is to achieve the Fast-Track targets.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, temporary residents from countries with a reciprocal healthcare agreement (RHCA) with Australia (i.e., Belgium, Finland, Italy, Malta, Netherlands, New Zealand, Norway, Ireland, Slovenia, Sweden, and United Kingdom) are eligible for subsidised access through Medicare. However, migrants outside of these categories are not eligible for Medicare, although some may access HIV care and treatment through compassionate access programmes or private health insurance [6,8]. When reporting HIV diagnosis and care cascades, it is important to provide subpopulation cascades to track progress toward Fast-Track targets and ensure no one is left behind.…”
Section: Introductionmentioning
confidence: 99%